2015
DOI: 10.1080/00222933.2015.1062930
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of invertebrate and aquatic plant communities at three intermittent ponds in livestock grazed Patagonian wetlands

Abstract: Ponds are recognized worldwide as biodiversity hotspots; nevertheless in Patagonia studies are still needed that reveal the composition and status of their communities. This paper analyses the temporal patterns of aquatic invertebrates and assesses the environmental factors that best predict the variation in community structure at three small intermittent ponds, subjected to ranching practices (summer stocking) in the Patagonian steppe. Variables identified as important in structuring community assemblages wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
6
1
4
Order By: Relevance
“…Inspection of weather conditions a posteriori revealed that both sampling periods were comparable in terms of rain, air temperature, and wind [ 20 ]. Surveys were conducted in early summer, the optimal season for obtaining samples representative of local invertebrate diversity and consisting of mature, readily identifiable individuals [ 21 ]. Moreover, the natural recharge of pond at wetlands occurs during seasonal rainfalls in winter, and the local ranching practices involve rotating livestock to wetlands in summer for reproductive periods and weaning.…”
Section: Methodsmentioning
confidence: 99%
“…Inspection of weather conditions a posteriori revealed that both sampling periods were comparable in terms of rain, air temperature, and wind [ 20 ]. Surveys were conducted in early summer, the optimal season for obtaining samples representative of local invertebrate diversity and consisting of mature, readily identifiable individuals [ 21 ]. Moreover, the natural recharge of pond at wetlands occurs during seasonal rainfalls in winter, and the local ranching practices involve rotating livestock to wetlands in summer for reproductive periods and weaning.…”
Section: Methodsmentioning
confidence: 99%
“…Research conducted on ponds in Patagonia showed that the concentrations of nutrients were good indicators of the state and quality of water. The content of nutrients in ponds affected by sewage should be higher than in more isolated ponds [65].…”
Section: Discussionmentioning
confidence: 86%
“…Sobre la base de esas imágenes se seleccionó y muestreó un total de 20 lagunas someras (Tabla 1). Las lagunas fueron muestreadas en una única ocasión entre diciembre de 2013 y enero de 2014, ya que en la región resulta el período más apropiado para estudiar tanto la composición de las macrófitas (e.g., fenología y presencia de flores), como para estimar su abundancia (Epele and Miserendino 2015).…”
Section: Selección De Sitios De Muestreounclassified